Risk Factors Analysis of Malaria Transmission at Cross-Boundaries Area in Menoreh Hills, Java, Indonesia - Dwi Sarwani Sri Rejeki; Solikhah Solikhah; Siwi Pramatama M Wijayanti (Tehran University of Medical Sciences, 2021)
Abstract Background: Risk factors of Malaria transmission at cross-boundaries area is important to be identified. This study aimed to identify the risk factors of Malaria transmission at cross-boundaries area in Menoreh Hills, Java, Indonesia. Methods: The design of the study was an observational study with a case-control design. Data on malaria cases and controls were obtained from the Primary Health Care in Menoreh. All malaria positive patients with clinical and laboratory examinations recorded in health services during 1 Jan 2015-31 Dec 2015. Overall, 138 cases and 138 controls were included. Several variables were collected such as altitude, night out behavior, the use of mosquito nets, nighttime bed, travel history, mosquito bite prevention activities, cattle ownership, distance to mosquito breeding site, etc. Data were obtained by structured questionnaires and observation. Data were analyzed by univariate, bivariate and multivariate Results: The altitude of house >500 m above sea level proved to be influential as a risk factor for Malaria (OR 3.62, 95% CI 1.61-8.16, P=0.002). Several variables were identified as a risk factor of Malaria such as the wall of the house from bamboo/wood, no insecticide and distance of house <100 m from mosquito breeding site. Conclusion: An awareness for the local health sector particularly to provide a recommendation for house construction to protect a community from Malaria transmission.